2002
DOI: 10.1074/jbc.m208540200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydration in the Binding of lac Repressor to DNA

Abstract: The osmotic stress technique was used to measure changes in macromolecular hydration that accompany binding of wild-type Escherichia coli lactose (lac) repressor to its regulatory site (operator O1) in the lac promoter and its transfer from site O1 to nonspecific DNA. Binding at O1 is accompanied by the net release of 260 ؎ 32 water molecules. If all are released from macromolecular surfaces, this result is consistent with a net reduction of solvent-accessible surface area of 2370 ؎ 550 Å 2 . This area is only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 67 publications
6
49
0
Order By: Relevance
“…To determine whether the previously observed effect of sucrose on DHF binding (10) arises solely from perturbations on water activity, osmolytes with different characteristics were used. For example, addition of glycine betaine or sucrose can both affect water activity, yet these molecules either increase or decrease the dielectric constant of the solution, respectively (30,35,36). If both compounds show similar results, then effects on the dielectric constant are not involved.…”
Section: Role Of Water In K Cat /K M(dhf)mentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether the previously observed effect of sucrose on DHF binding (10) arises solely from perturbations on water activity, osmolytes with different characteristics were used. For example, addition of glycine betaine or sucrose can both affect water activity, yet these molecules either increase or decrease the dielectric constant of the solution, respectively (30,35,36). If both compounds show similar results, then effects on the dielectric constant are not involved.…”
Section: Role Of Water In K Cat /K M(dhf)mentioning
confidence: 99%
“…Here, the osmotically active volume depends on the size of the osmolyte, with larger osmolytes detecting changes in larger volumes. Osmotic stress occurs as the solution must compensate for this exclusion (30,31). A last possibility is the direct interaction of the osmolyte with either the ligand or protein (37,38).…”
Section: Role Of Water In K Cat /K M(dhf)mentioning
confidence: 99%
See 1 more Smart Citation
“…211 M in the presence of the same saline buffer but with 5% ethylene glycol. 24 More significantly, the dissociation constant was weaker than for a dsDNA fragment containing the pUC19 lac binding region (186 bp) interacting with a 64mer peptide which contained helices 1-4 (see Introduction) of 5.7 6 0.3 3 10 211 M 25 . Hence, it may be concluded that although the absence of helix III (residues 32-45) has a negligible effect on the overall dissociation constant, its absence appears to increase both the association and dissociation rates.…”
Section: 1)mentioning
confidence: 98%
“…22 The in vivo dissociation constant of the Lac repressor and the complete lac operator (lacO 1 , lacO 2 , and lacO 3 ) has been calculated as 1 3 10 213 M. 23 The in vivo dissociation constant of the Lac repressor and lacO 1 alone has been estimated as 5 3 10 210 to 1 3 10 29 M 13 and 1-1.2 3 10 210 M in the presence of a saline buffer and 2.9-3.9 3 10 211 M in the presence of the same saline buffer but with 5% ethylene glycol. 24 In a previous study, a 186 bp double stranded DNA fragment created from a pUC19 template and a 64mer peptide ligand containing the complete LacI DNA binding domain (helix I-helix IV) displayed a dissociation constant (K D ) of 5.7 3 10 211 M. 25,26 As the optimal dissociation constant for an affinity binding mechanism for use in a chromatographic system is 10 26 M-10 28 M (Natural Toxins Research Centre, 2001), all of these systems display a K D too low for a chromatographic or adsorption/desorption system such as would be employed in a biosensor. If the dissociation constant is greater than this value, nontarget molecules can be co-purified as the mechanism is normally not strong or selective enough for the target.…”
Section: Introductionmentioning
confidence: 97%